Relation between secondhand smoke exposure and cardiovascular risk factors in never smokers - Kim, Sehun (J Hypertens, 2017)
OBJECTIVE: Secondhand smoke exposure (SHSE) in nonsmokers has been associated with premature cardiovascular mortality and ischemic heart disease. We conducted a cross-sectional, population-based study evaluating the relationship between SHSE, measured by subjective and objective methods, and conventional cardiovascular risks such as blood pressure, lipid profiles, and fasting glucose. METHODS: We extracted information on 7376 healthy adults who had never smoked, for whom there were available urine cotinine levels, from the Korea National Health and Nutrition Examination Survey 2008–2011. SHSE was defined using self-report questionnaires and urine cotinine levels. The main outcomes included SBP and DBP, serum lipid profiles, and fasting glucose. RESULTS: The mean age of the study population was 45.4 ± 0.4 years and 75.2% were women. Self-reported SHSE had no significant association with study outcomes except for DBP, which had marginally positive relationships (P = 0.060). Unadjusted analysis showed higher cotinine levels were associated with lower SBP, total cholesterol, LDL cholesterol, and triglyceride. All associations lost statistical significance after multivariable adjustment. Fasting glucose had a positive relationship with urine cotinine in quartiles but not with logarithm-transformed cotinine. CONCLUSION: Although SHSE is associated with increased risk of cardiovascular mortality and morbidity, we did not find any consistent relationship among SHSE and blood pressure, lipid, or fasting glucose levels in this cross-sectional study. Using objective measurements of urine cotinine did not alter this relationship. Further long-term prospective studies are needed to evaluate the effect of SHSE as a cardiovascular risk factor.